2014
DOI: 10.5114/fn.2014.47846
|View full text |Cite
|
Sign up to set email alerts
|

Blood vessel ultrastructural picture in a CADASIL patient diagnosed at an advanced age

Abstract: A b s t r a c tWe report the case of an 84-year-old

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…As mice aged 6 months only showed stages I-III GOM, individual GOM deposits seem to increase in size and become increasingly amorphous over time, and new GOM seem to be continuously formed. This is further illustrated by the observation that GOM deposits of stage I and II are also present in post-mortem CADASIL patient brain microvessels, next to the more extensive GOM pathology, including patches of confluent GOM (stage V) [7,25,26].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…As mice aged 6 months only showed stages I-III GOM, individual GOM deposits seem to increase in size and become increasingly amorphous over time, and new GOM seem to be continuously formed. This is further illustrated by the observation that GOM deposits of stage I and II are also present in post-mortem CADASIL patient brain microvessels, next to the more extensive GOM pathology, including patches of confluent GOM (stage V) [7,25,26].…”
Section: Discussionmentioning
confidence: 91%
“…Brulin et al analysed GOM in skin biopsies of CADASIL patients of different ages, and found that the number GOM deposits increase up to 50 years of age, but also found that the number of GOM seems to decrease in elderly patients [11]. The latter may either be attributed to other endstage vessel wall changes hampering the visualization of GOM, or because GOM seem to become confluent and disintegrate over time [26]. Whether different GOM stages in skin biopsies of CADASIL patients are associated with disease severity and disease progression, therefore, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of multiple deposits of GOM at ultrastructural examination of brain or skin vessels is the pathognomonic hallmark of CADASIL [1,8,11], with 100% specificity and 96% sensitivity [7]. Nevertheless, the origin, chemical nature and function of GOM deposits are still not clear.…”
Section: Abstract: Cadasil Notch3 Granular Osmiophilic Material Gmentioning
confidence: 99%
“…As the majority of the mutation is present in exon 4 of NOTCH3, the genetic analysis should begin from screening this exon, and later should be extended to exons 2, 3, 5, 6 and 11 [20]. Mutations only in exons 3, 4, 6, 8 and 12 of NOTCH3 have been identified in Polish CADASIL patients so far [2,7,[21][22][23]. The mutations in exon 4 of the NOTCH3 gene found in Polish patients include R133C [22], C185R and C212G [7].…”
Section: Discussionmentioning
confidence: 99%